Pengembangan Aplikasi Aok-Jek Menggunakan Kerangka Kerja COBIT 4.1 Untuk Meningkatkan Pelayanan Terhadap Pelanggan - Agus Dendi Rachmatsyah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2018)
The development of technology today can not be dammed again. Progress in every field can not be separated from technology as its supporting, especially information technology. Information technology (IT) is a very important part for the company or organization and is an investment value to make the company or organization to be better. Companies or organizations put information technology as a thing that can support the achievement of the company's strategic plan to achieve the target vision, mission and goals of the company or organization, but it must be taken with the existence of an analysis or audit of the information system so that threats or losses can be avoided or prevented. This studi aims to determine the extent to which the development of Aok-Jek Application system as a public service that has been implemented in the community. AOK-JEK is a local online ojek service application in Bangka Belitung which was launched in early January 2017. AOK-JEK itself is the development of online ojek service via sosmed to be an android app. Aok-jek provides services and needs in various fields for the community. The first thing that makes us interested and motivated to analyze the application is one of the journal writers, AOK-JEK.